THE SELECTION OF PRODUCTIVITY KEY PERFORMANCE INDICATORS FOR CAR MANUFACTURING COMPANIES USING INTEGRATED PERFORMANCE MEASUREMENT SYSTEM - Uly Amrina; Alfa Firdaus (SINERGI, 2018)
The increase in car market 17% in 2020, and ASEAN Free Trade policy only 5% for imported products, cause tightened competition in the automotive market. Car manufacturing companies face problems in selecting their performance indicators related to competitive challenges. The purpose of this research is to develop productivity key performance indicators in car manufacturing that conform to stakeholder requirements as a strategy to win the market. The conditions are manifested in a mapping of manufacturing symbols using the Integrated Performance Measurement System (IPMS) method. That manufacturing productivity indicators will become the focus of the top management to be controlled. There are four stages to go through, starting with the identification of stakeholder requirement, which produces six criteria and 12 stakeholder requirements and mapped into 16 goals and 24 key performance indicator (KPI). The second stage is benchmarking, and preparation of KPI hierarchy and the third stage is the description of each KPI in the form of KPI specification table. The fourth stage is the weighting of the six main criteria that result in 3 priority criteria which must be reported monthly between the manufacturing division (painting), finance and administration. Those are employee safety, manufacturing process effectiveness (painting) and waste elimination activities. The priority is obtained based on questionnaires answered by ten stakeholders (experts) processed with Analytical Hierarchy Process (AHP) approach and has been tested consistency in the number 0.09. These three criteria are described in 15 KPIs: performance rate, availability rate, quality rate, trained operator ratio, training value ratio> 80, delay ratio, attendance ratio, downtime losses, setup and adjustment losses, idle time, defect losses, yield losses, manpower efficiency, environmental impact and work accident ratio.